2017
DOI: 10.1016/j.joto.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

“Wait and scan” management of patients with vestibular schwannoma and the relevance of non-contrast MRI in the follow-up

Abstract: Vestibular schwannoma (VS) is a slow-growing benign neoplasm. There has been an evolution in the management of VS from active treatments (microsurgery and stereotactic radiotherapy) to conservative management (wait and scan). Regular MRI scanning is necessary to monitor tumor progression. Conservative management causes significantly less complications and offers a higher quality of life compared with active treatments. The mean growth rate of VS varies from 0.4 to 2.9 mm/year, and spontaneous shrinkage is obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 87 publications
(128 reference statements)
0
19
0
1
Order By: Relevance
“…Kichman et al reported that in their cohort, 37% of vestibular schwannomas exhibited tumor growth and 15% required invasive treatment during the 10-year follow-up period [13]. Zou et al noted that conservative management using the “wait and scan” method was suitable for 87% of vestibular schwannomas [14]. Surgery is therefore not currently recommended immediately after tumor diagnosis in asymptomatic vestibular schwannomas [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kichman et al reported that in their cohort, 37% of vestibular schwannomas exhibited tumor growth and 15% required invasive treatment during the 10-year follow-up period [13]. Zou et al noted that conservative management using the “wait and scan” method was suitable for 87% of vestibular schwannomas [14]. Surgery is therefore not currently recommended immediately after tumor diagnosis in asymptomatic vestibular schwannomas [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al noted that conservative management using the “wait and scan” method was suitable for 87% of vestibular schwannomas [14]. Surgery is therefore not currently recommended immediately after tumor diagnosis in asymptomatic vestibular schwannomas [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Світові тенденції і наш підхід полягає в активній хірургічній тактиці, спрямованій на максимально можливе видалення новоутворення з урахуванням як анатомічного, так і функціонального збереження залучених ЧН. Щодо пацієнтів похилого та старечого віку зі шванномами малого розміру (І-ІІ за Koos) з мінімальною симптоматикою чи безсимптомними, у яких висока вірогідність відсутності росту новоутворення [20][21][22], тактика зазвичай полягає в динамічному спостереженні з періодичним МРТ-контролем.…”
Section: Resultsunclassified
“…Various treatment and management strategies are available, varying from surgical resection, stereotactic radiosurgery and conservative observation (‘wait and scan’). 4–6…”
Section: Introductionmentioning
confidence: 99%